Improving Customer Loyalty Lion Air's Influenced By Customer Experience and Airline Reputation - Uce Karna Suganda; Della Ayu Marista (Budapest International Research and Critics University, 2022)
The aviation service industry in Indonesia has the lowest level of loyalty compared to other industries. This condition is suspected to be related to problems related to customer experience, as well as reviewing the reputation of the airline, loyal customers of national airlines in Indonesia; and the influence of airline reputation, on customer experience and on customer loyal coustomer. This study uses a quantitative approach. The unit of analysis is a national airline company that has issued a customer relationship management program consisting of 3 airlines, namely Lion Air. The unit of observation is more than one airline passenger. The time horizon in this study is cross sectional. Primary data collection was done by questionnaire to 300 respondents with purposive sampling technique. The verification analysis was carried out using the Structural Equation Modeling (SEM) model. The findings show that the airline's reputation is not high, price attractiveness is perceived as attractive, and customer loyal coustomer is not high. Airline reputation does not have a positive influence, while customer relationship management and price attractiveness have a positive influence on the loyal coustomer of airline customers. Customer experience has a positive influence on the loyal coustomer of airline customers in Indonesia. .